Kampung Ramah Lingkungan Sebagai Aset Pengembangan Teknologi Sumber Daya Alam Di Desa Tlajung Udik Kecamatan Gunungputri Kabupaten Bogor - Muhammad Ikhsan Ghofur; Estriana Arifah Mahfud (UIN Siber Syekh Nurjati Cirebon, 2022)
In an effort to develop the village, adequate apparatus of village government institutions and people who have a high sense of belonging are needed for the progress of their village. What is really needed by the Village is the need for assistance from various cross-sectoral elements, especially the Regional Government as a sector field for the village government. Tlajung Udik Village is one of the villages in the Gunung Putri District, Bogor Regency. In fulfilling the Development of Natural Resources Technology, the village of Tlajung Udik conducts program development for the surrounding community, namely the Environmentally Friendly Village (KRL). The purpose of an environmentally friendly village is to encourage local governments, business actors and local communities to understand environmental problems and their impacts, and take proactive actions that contribute to environmental protection and management efforts. This research was conducted using a qualitative method, which is able to understand and describe how the implementation of the Environmentally Friendly Village Program is using interview, observation, and documentation techniques. The results of this study revealed that in Tlajung Udik Village the implementation of the Environmentally Friendly Village Program had a positive impact such as optimizing the return function, controlling the separation of organic and non-organic waste, making hydroponics as a decoration for houses and small alleys, therefore the KRL program for this community is expected can be an example for other villages in Bogor Regency.